Granulation of mefenamic acid and poly-ethylene glycol (PEG) using pressure swing granulation (psg) technique in fluidized bed [Pembentukan granul berasaskan asid mefenamik dan polietilena glikol (PEG) menggunakan teknik pengranulan tekanan terayun dalam turus terbendalir] - Ab Ghani, Salinda; Abu Bakar, Noor Fitrah; Abu Bakar, Mohd Rushdi; Yusof, Yus Aniza; Abdul Rahman, Norazah (Faculty of Science and Technology, Universiti Kebangsaan Malaysia, 2018)
Granulation of mefenamic acid particles was conducted to produce spherical shape, narrow size distribution of granules, high granule strength and good content uniformity by using Pressure Swing Granulation (PSG) technique in a fluidized bed. Two types (binderless and with binder) of granules namely lactose-mefenamic acid (MA) and lactose-polyethylene glycol (PEG)-(MA) with mass ratio of 30:70 and 25:5:70 were produced respectively. The later type of granules was heated for 80 ˚C, above the PEG melting point. Results indicated that all granules were uniform, spherical and narrow size distribution with the average granules size was less than 500 μm. The tensile strength of the lactose-PEG-MA was higher than the lactose-MA due to heating process. The tensile strength of lactose-PEG-MA and lactose-MA with average granules size of 500 μm were 0.42 MPa and 0.33 MPa, respectively. The drug contents in both types of granules were uniform i.e. around 70 ± 0.3 wt.%.